Experimental study of injector based on the spark source with titanium cathode saturated with hydrogen - Vasiliev, A.A.; Iosseliani, D.D.; Kushin, V.V.; Petrenko, S.V.; Plotnikov, S.V.; Seleznev, D.N.; Zubovsky, V.V.; Bogolyubov, E.P.; Bobylev, V.T.; Kuznetzov, V.A.; Ryzhkov, V.I.; Presnyakov, Yu.K.; et al. (Вопросы атомной науки и техники, 2004)
The results of experimental study of short-pulse proton injector for various variants of construction of pulse spark ion source are considered. The experimental results of study of regimes of both ignition and discharge support within the source with stabilized pulse feeding (~10 μs, 5 Hz). Of special concern the increasing of the cathode electrode lifetime. The results ofmeasurements ofboth absolute and partial (in spices) density ofion beam are presented.